If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
13/10 = (2*x)/10-(1*x) // - (2*x)/10-(1*x)
1*x-((2*x)/10)+13/10 = 0
(-1/5)*x+x+13/10 = 0
4/5*x+13/10 = 0 // - 13/10
4/5*x = -13/10 // : 4/5
x = -13/10/4/5
x = -13/8
x = -13/8
| y^2-12y+14=0 | | 28-8x+10x=20-6x+8x | | 4x-19=3x+9 | | -9=u-2 | | 12k+6k^2+k^3+8=64 | | 3a+3=5s-7 | | x(x-3)(x-3)=4.8 | | Cos(2x)-3cos(x)-1=0 | | x=3-28 | | 3f-6=2t+2 | | 2i-3=i+14 | | 4x+5=-2x+5 | | 5+6x=x+7 | | (4x+6)+(-5x+2)= | | 2=6x+13x-6 | | 26-n=11 | | z^2+3*z+6=0 | | =13000 | | 4x-7=3(2x+5)-2 | | x^6+7x^5+21x^4+35x^3+35x^2+21x=1064640 | | a=3.14*d | | In(x-1)+(x+2)=1 | | x^3-9x-400=0 | | x+10=61 | | Y+3x=28 | | 3=v-5/3 | | 2sin(2teida)=0 | | (x+7)(2x-7)=0 | | 2x-3=0.5x | | 4(3z-1)-5(z+6)=4(z+1) | | (12-3x)/(2sqrt(6-x)=0 | | (12-3x)/(2√(6-x))=0 |